(untitled) (Ustozlar uchun, 2024)
Annotation The article delves into contemporary trends within the global evolution of pension systems, which constitute a vital component of the financial infrastructure. It centers on enhancing Uzbekistan's pension system by drawing insights from the experiences of advanced European nations, offering perspectives and suggestions on potential improvements.